Production of welan gum from cane molasses by Sphingomonas sp. FM01. (15th September 2020) - Li, Qiwen; Zhou, Yuan; Ke, Chengzhu; Bai, Yunxia; Liu, Xiaoling; Li, Shubo
Highlights: In this article "Production of Welan gum from cane molasses by Sphingomonas sp. FM01", the highlights. Sphingomonas sp. FM01 could produce 37.65 g/L ofwelan gum using cane molasses as the carbon source. Molasses-produced welan gum had an acceptable molecular weight and better viscosity stability. Molasses-produced welan gum could maintain excellent rheological properties under high osmotic pressure. Abstract: As an extracellular exopolysaccharide, welan gum could serve as a suspending agent, stabilizer, emulsifier and thickener with characteristics that include bio-adhesion, non-toxicity, biocompatibility and biodegradability. In this study, Sphingomonas sp. FM01 was applied to effectively produce welan gum using cane molasses as the carbon source. After pretreatment with phosphoric acid and polyacrylamide, 60 g/L cane molasses combined with 6.0 g/L beef extract, 3 g/L KH2 PO4, 0.5 g/L MgSO4, 15 mmol/L H2 O2 and 4 mg/L niacin significantly improved the fermentation performance of Sphingomonas sp. FM01, increasing the production of welan gum to 37.65 g/L. Investigation of the rheological behavior of the welan gum obtained from the molasses-welan gum mixture showed it had an acceptable molecular weight and similar rheological properties and better viscosity stability compared to that obtained from sucrose, indicating that cane molasses could be explored as a suitable and inexpensive substrate for cost-effective welan gum production.